Ninguém nascia e ninguém morria em Canaã, Ceará: registro tardio, o reconhecimento de paternidade e a construção da cidadania - Machado, Fábio Henrique Mendes (My University, 2025)
The present dissertation addresses the relationship between late birth egistration, paternity recognition, and the construction of citizenship in the district of Canaã, Ceará. This topic is particularly relevant in the context of small Brazilian towns, characterized by historical and structural challenges in accessing fundamental rights. In a reality where the absence or delay of these civil records undermines access to basic services, social integration, and the full exercise of citizenship, this study reflects on the implications of such a scenario for promoting inclusion and equality. Within this context, the primary objective of this research was to investigate how these gaps affect the construction of citizenship in Canaã, while the specific objectives aimed to understand the historical development of the concept of citizenship, analyze the obstacles faced by rural communities in accessing civil rights, and propose practical solutions, such as the creation of an educational booklet, to mitigate these barriers. To achieve these goals, the adopted methodology combined bibliographic research and document analysis with the development of an educational booklet. The bibliographic review provided the necessary theoretical foundation, based on works by historians and legal scholars discussing the concept of citizenship and its dimensions. Document analysis, in turn, focused on civil records from Canaã, offering a practical understanding of the local dynamics and the challenges faced by the population. Subsequently, the booklet, developed with accessible language and practical content, represented an effort to translate academic knowledge into a product with direct social impact. The results demonstrated that late birth registration and paternity recognition have both individual and social impacts, hindering access to basic rights and contributing to the marginalization of certain groups. The educational booklet, conceived as the final product, proved to be a tool with the potential to address awareness gaps within the community by presenting legal information in a simplified manner. Thus, it informs and raises awareness among the population about the importance of civil registration, facilitating access to these rights. [resumo fornecido pelo autor]
A presente dissertação aborda a relação entre o registro tardio de nascimento, o reconhecimento de paternidade e a construção da cidadania no distrito de Canaã, município de Trairi, estado do Ceará, tema que adquire relevância no contexto das pequenas cidades brasileiras, marcadas por desafios históricos e estruturais no acesso a direitos fundamentais. Inserido em uma realidade onde a ausência ou atraso desses registros civis compromete o acesso a serviços básicos e a integração social e o exercício pleno da cidadania, o estudo propõe uma reflexão sobre as implicações desse cenário para a promoção da inclusão e da igualdade. Nesse contexto, o objetivo geral do trabalho foi investigar como essas lacunas impactam a construção da cidadania em Canaã, enquanto os objetivos específicos visaram compreender o desenvolvimento histórico do conceito de cidadania, analisar os obstáculos enfrentados por comunidades rurais no acesso aos direitos civis e propor soluções práticas, como a elaboração de uma cartilha educativa, para minimizar essas barreiras. Para atingir tais objetivos, a metodologia adotada combinou pesquisa bibliográfica e análise documental com a elaboração de uma cartilha educativa. A revisão bibliográfica forneceu o embasamento teórico necessário, fundamentado em obras de historiadores e juristas que discutem o conceito de cidadania e suas dimensões. A análise documental, por sua vez, baseou-se nos registros civis de Canaã, permitindo uma compreensão prática das dinâmicas locais e das dificuldades enfrentadas pela população. Posteriormente, a elaboração da cartilha, desenvolvida com linguagem acessível e conteúdo prático, representou o esforço de tradução do conhecimento acadêmico em um produto de impacto social direto. Logo, os resultados demonstraram que o registro tardio de nascimento e o reconhecimento de paternidade possuem impactos no plano individual e no social, dificultando o acesso a direitos básicos e contribuindo para a marginalização de determinados grupos. A cartilha educativa, concebida como produto final, mostrou-se ser uma ferramenta com potencial de preencher lacunas de conscientização na comunidade por meio da apresentação de informações jurídicas de forma simplificada, assim, informando e sensibilizando a população sobre a importância do registro civil e facilitando o acesso a esses direitos. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Direitos humanos; Registro civil - Ceará; Cidadania; Integração social; History - Study and teaching; Human rights; Registers of births, etc. - Ceará; Citizenship; Social integration